The orchid house : a novel - Riley, Lucinda (New York : Atria Books, 2012)
"For fans of The House at Riverton and Rebecca--a debut spanning from the 1930s to the present day, from a magnificent estate in war-torn England to Thailand, this sweeping novel tells the tale of a concert pianist, Julia, and the prominent Crawford family whose shocking secrets are revealed, leading to devastating consequences for generations to come. As a child Julia Forrester spent many idyllic hours in the hothouse of Wharton Park, the great house where her grandfather tended exotic orchids. Years later, while struggling with overwhelming grief over the death of her husband and young child, she returns to the tranquility of the estate. There she reunites with Kit Crawford, heir to the estate and her possible salvation. When they discover an old diary, Julia seeks out her grandmother to learn the truth behind a love affair that almost destroyed Wharton Park. Their search takes them back to the 1930s when a former heir to Wharton Park married his young society bride on the eve of World War II. When the two lovers are cruelly separated, the impact will be felt on generations to come. Lucinda Riley skillfully sweeps her readers between the magical world of Wharton Park and Thailand during World War II with irresistible and atmospheric storytelling. Filled with twists and turns, passions and lies, and ultimately redemption, The Orchid House is a romantic, poignant novel that became an instant bestseller in the UK and Germany"--
Originally published: The hothouse flower. London : Penguin Books, 2011.
Keywords: Women pianists -- Fiction; Family secrets -- Fiction; Country homes -- England -- Fiction; World War, 1939-1945 -- Fiction; FICTION / Historical; FICTION / Literary; FICTION / General; Thailand -- Fiction